GENDER-DIVERSE IDENTITY AND SOCIAL ACCEPTANCE IN CONSERVATIVE SOCIETIES (Contemporary Journal of Social Science Review, 2025)
The social acceptance of gender-diverse identities in conservative societies is a theoretical debate and policy concern across the societies. Social structures and processes shapes individual perception about the acceptance of gender-diverse identities. This study thus investigates the relationship between gender-diverse identities and social acceptance in conservative societies where traditional norms and cultural values dominates individual’s perception of accepting diverse gender identities. A fixed quantitative research design is adopted in this study to objectively quantify the relationship between gender-diverse identities and its social acceptance across the conservative societies. This study has specifically examined individual acceptance of diverse gender-diverse identities with specific focus on different factors, such as age, education level, religious beliefs, and exposure to gender diversity. Using a structured questionnaire, data were collected from 400 respondents. Through stratified random sampling technique, participants were recruited from different age groups and educational backgrounds who belonged to conservative cultural contexts. Inferential statistics, including Pearson correlation and multiple regression analysis were used to objectively identify significant predictors that establish a relationship between the social acceptance and gender-diverse identities. Findings of the study revealed a low-level of acceptance for the diverse and non-conformed gender identities among old age people. However, the acceptance level of diver’s gender identities among younger and educated respondents was high. In order to ensure social integration across the gender diverse-groups this study recommends launching awareness programs and designing inclusive policies to eliminate discrimination against gender-diverse identities.